EFFECT OF MORINGA OLEIFERA LEAVES ON HEMATOLOGICAL AND SERUM CHEMISTRY ATTRIBUTES OF APPARENTLY HEALTHY RABBIT DOES - Umer Farooq; Zia-Ur-Rehman; Madiha Sharif; Mushtaq Hussain Lashari; Musadiq Idris; Mujahid Hussain; Muhamad Wasim Tasleem (Journal of Animal and Plant Sciences, 2023)
The study was designed to assess the effect of Moringa oleifera leaf extract on various hematological and serum chemistry attributes (liver and kidney function test enzymes) of apparently healthy rabbit does (n=24), either positive or negative. The animals were divided in four groups namely A, B, C and D (n=6 rabbits/group). First group was considered as control group provided with basal diet and water without any supplementation. Group A, B and C were considered as treatment groups which were provided with basal diet, water and supplementation of M. oleifera crude leaf aqueous extract at the dose rates of 150mg/kg, 300mg/kg, and 450 mg/kg, respectively. On day 10, 20, 30 and 40, blood samples were collected from all animals. The blood samples (n=96) were analyzed through hematology analyzer and semi-automatic chemistry analyzer. Results regarding hematological attributes revealed that the Mitotic Index was significantly (P≤0.05) higher in control group whereas Red Cell Distribution Width Count was significantly (P≤0.05) higher in Group C as compared to their counterpart groups. Similarly, Total Erythrocytic Count was significantly (P≤0.05) higher in Group B. The creatinine, urea and blood urea nitrogen differed significantly (P≤0.05) while Uric acid showed non-significant (P≥0.05) difference between the groups. It is concluded that varying doses of Moringa do not exert any untoward effect on hematochemical attributes of rabbits and hence their health. Rather, positive effects were noticed at dose rate of 150mg/kg.
Keywords: M. oleifera; Hematology; Liver Function Test; Kidney Function Test